HUBUNGAN FAKTOR LAMA MENDERITA DM DAN TINGKAT PENGETAHUAN DENGAN DISTRES DIABETES PADA PENDERITA DIABETES MELLITUS TIPE 2 TAHUN 2017 (Studi di Wilayah Kerja Puskesmas Rowosari, Kota Semarang) - Fitrianur Laili; Ari Udiyono; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Distress Diabetes was a condition that was common in people with diabetes. As many as 48.5% of people with type 2 diabetes were at risk of developing diabetic distress. The purpose of this study was to describe and analyze the relationship between duration of DM and level of knowledge with distress diabetes in type 2 DM patients in 2017. The population were all type 2 Diabetes Mellitus patients recorded at Rowosari Public Health Center, Semarang City in 2017, namely 231 patients. The minimum sample size was 100 respondents with a simple random sampling method. And for data analysis used sperman rank test with 95% significance level. The results showed that the average duration of DM was 4.66 years, the average level of knowledge was 4.33 points, and the average score of diabetic distress was 51.16 points. As for the significance value for the duration of DM variable (p = 0.005; rp = -0.280) and level of knowledge variable (p = 0.001; rp = -0,654). So the conclusion of this study that there was a significant relationship between the duration of DM variable and level of knowledge variable with diabetes distress.